Intervertebral discs degeneration and methods of its biological correction - Vasilyeva, I. G.; Khyzhnyak, M. V.; Shuba, I. N.; Gafiychuk, Yu. G. (Ukrainian Neurosurgical Journal, 2010)
Human physical possibilities limitation caused by intervertebral discs degenerative diseases is a serious medical and social problem in our time. Main signs of intervertebral discs degenerative diseases — cells death, proteoglycane and collagen synthesis decrease. Intervertebral discs degeneration is frequent cause of painful syndrome forming. Today therapy is directed not only on painful syndrome elimination but also on dick’s functions renewing. Modern technologies are frequently based on biological materials using. Injections of proteins activators, biomaterials, different cell types or cell complexes and extracellular matrix, genetically modified cells, and in vitro constructed tissue are used for intravertebral disc regeneration activation. Using one or another therapeutic tactic sufficiently depends on degenerative state expressivity, taking into account the procedure safety.